Skrifter udgivet af Grundtvig-Selskabet - Lundgreen-Nielsen, Flemming; Michelsen, William; Schjørring, Jens Holger; Pedersen, Kim Arne (Grundtvig-Studier, 1996)
Works published by the Grundtvig Society